Annotated temporal logics Delta*tau - Abe, J. M. (2000)
In this paper we present a class of paraconsistent temporal system Delta*tau which may constitute, for instance, a framework for paraconsistent temporal reasoning. We establish the completeness of Delta*tau using the Kripke semantics. The proposed temporal logic subsumes the classical one with the advantage of handling inconsistency.